Merantau dalam Menuntut Ilmu (Studi Living Hadis oleh Masyarakat Minangkabau) - Yeni Angelia; In'amul Hasan (Jurnal Living Hadis, 2017)
Demanding knowledge is a must for every muslim and muslimah. There are many ways to gain knowledge, especially at this time. The Minangkabau people make wander as a culture and a very supportive method in the process of studying. The process resulted a tradition that related or based on the Prophet's hadith. This phenomenon has occurred since Islam entered Minangkabau, so it’s called by living hadith. Go out from native city or wander to get some knowledge outside, is a proof that Islam has entered Minangkabau. And it is recorded in history that Shaykh Ahmad Khatib al-Minangkabawi has done wander in studying to Masjid al-Haram and became khadim there at the end of the 19th century.